(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Nephrotoxicity is an important side effects of captopril and gentamicin. This study investigated the prophylactic and protective effects of pomegranate juice (PJ) on the kidney exposed to nephrotoxicity induced by these medications. Materials and Methods. Wistar male rats received drinking water (groups 1 to 3) or PJ at doses of 4 mL/kg (group 4), 10 mL/kg (groups 5 and 7), and 15 mL/kg (group 6) for 14 days. Captopril and gentamicin were administrated on days 10 and 14 to groups 1 and 2, respectively, while groups 3 to 6 received both. Group 7 did not receive anything. The serum, urine, and renal tissue parameters were measured after the experiment. Results. Group 1 (captopril) had a higher malondialdehyde level than groups 4, 5, 6, and 7 with PJ (P <0.05), and group 3 (captopril and gentamicin) showed the most significant malondialdehyde level compared to other groups (P < .001). Group 5 (captopril, gentamicin, and PJ, 10 mL/kg) had the most significant sodium excretion compared to other groups (P < .001), and group 2 (gentamicin) showed the highest potassium absolute excretion (P < .001). The instability of the renal index was observed during the experiment for the groups receiving drinking water, while no significant changes were observed in the groups receiving PJ. Conclusions. The prophylactic consumption of PJ for 14 days could show nephroprotective effects by reducing oxidative stress and potassium depletion. It could also lead to the stabilization of kidney function during this period despite using captopril and gentamicin.